Direct graphene synthesis on LiNbO3 substrate by C implantation on Cu covering layer. (1st November 2022) - Xu, Yuhang; Lu, Fei; Liu, Yifan; Ma, Changdong
Abstract: We directly synthesized multi-layer graphene with an area of several hundred square microns on the lithium niobate (LN, LiNbO3 ) substrate by Carbon (C) implantation into the copper (Cu)-covered LiNbO3 . The energy of C ion implantation was optimized per SRIM simulation to ensure that the distribution of C covers the Cu/LiNbO3 interface. The optimized energy was established at 55 keV, such that the formation of C peaks in the respective materials on each side of the Cu/LiNbO3 interface. The diffusion of the accumulated C to the Cu/LiNbO3 interface can form a more uniform C distribution at the interface, which is beneficial to the synthesis of graphene. Following the annealing process and removal of the Cu coating, a multi-layer graphene with an area of several hundred square microns on the surface of LiNbO3 was identified and characterized using Scanning Electron Microscopy (SEM), Energy-Dispersive x-ray Spectroscopy (EDS), Raman spectroscopy, and Atomic Force Microscopy (AFM). This remarkable advancement encourages the industrialization of direct graphene synthesis on LiNbO3 substrates via ion implantation.